1985
DOI: 10.1056/nejm198503143121101
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Results of a Randomized Clinical Trial Comparing Total Mastectomy and Segmental Mastectomy with or without Radiation in the Treatment of Breast Cancer

Abstract: In 1976 we began a randomized trial to evaluate breast conservation by a segmental mastectomy in the treatment of Stage I and II breast tumors less than or equal to 4 cm in size. The operation removes only sufficient tissue to ensure that margins of resected specimens are free of tumor. Women were randomly assigned to total mastectomy, segmental mastectomy alone, or segmental mastectomy followed by breast irradiation. All patients had axillary dissections, and patients with positive nodes received chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
530
1
37

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,778 publications
(583 citation statements)
references
References 20 publications
15
530
1
37
Order By: Relevance
“…Whereas a radical or modified radical mastectomy used to be the standard treatment, it is now clear that in appropriate cases breast-conserving treatment achieves equivalent long-term survival rates (Veronesi et al, 1981;Sarrazin et al, 1983;Fisher et al, 1985;Van Dongen et al, 1991;Lichter et al, 1992). Furthermore, in the past 10 years it has become increasingly apparent that systemic adjuvant therapy following surgery leads to a reduction in recurrence rates and mortality (Early Breast Cancer Trialists' Collaborative Group, 1992).…”
mentioning
confidence: 99%
“…Whereas a radical or modified radical mastectomy used to be the standard treatment, it is now clear that in appropriate cases breast-conserving treatment achieves equivalent long-term survival rates (Veronesi et al, 1981;Sarrazin et al, 1983;Fisher et al, 1985;Van Dongen et al, 1991;Lichter et al, 1992). Furthermore, in the past 10 years it has become increasingly apparent that systemic adjuvant therapy following surgery leads to a reduction in recurrence rates and mortality (Early Breast Cancer Trialists' Collaborative Group, 1992).…”
mentioning
confidence: 99%
“…The only area where there was > 80% consensus on management was in the treatment of the primary tumour, where most surgeons now agree that the primary tumour (in selected patients) can be treated safely by local excision as opposed to mastectomy. It must be emphasised that the major reason that this consensus has arisen is because of the publication of the results of large randomised clinical trials (9,10). In our study it can be seen that breast cancer is managed in most hospitals by more than one consultant.…”
Section: Discussionmentioning
confidence: 71%
“…The publication of these studies resulted in a change in the surgical management of breast cancer in this country. In 1984, Gazet et al (11) showed that 84% of surgeons in England and Wales would regularly perform mastectomy, but by 1987 Morris et al (12) had shown that this figure had fallen to 43%, and in a follow-up study in 1991 (13) 10 Whether the surgeon performed regular follow-up investigations on their breast cancer patients (eg bone scans) if the patient remained asymptomatic. 11 The frequency that the surgeon would perform mammography after breast-conserving surgery and radiotherapy for breast cancer.…”
mentioning
confidence: 99%
“…The following verbatim transcript shows Roundsman discussing the relevance of a publication by Fisher [11]. "Fisher85a was a randomized, controlled trial conducted at multiple NSABP centers.…”
Section: Examplementioning
confidence: 99%